PERBAIKAN JATUH TEGANGAN DAN RUGI DAYA PADA PENYULANG 2 BELANDA SUB PENYULANG BUKIT KAPUR DI UP3 DUMAI MENGGUNAKAN 3 KAPASITOR BANK - Pangeran Fatullah; Teguh Utomo; Unggul Wibawa (Jurnal Mahasiswa TEUB, 2022)
In the Belanda feeder the Bukit Kapur sub feeder has a total channel length of 96,777 kms and PT. Harap Panjang has quite a lot of inductive loads, so the use of electrical energy consumed by PT. Harap Panjang on the Belanda feeder is getting bigger. So drop voltage and power losses often occur in the Belanda feeder the Bukit Kapur sub feeder. Therefore, improvements were made using a capacitor bank through the ETAP 16.0 software. The results of the first analysis showed that the drop voltage on the Belanda feeder the Bukit Kapur sub feeder was 11.58% and the power loss was 232.2 kW and 263.2 kVAR. The improvement of the drop voltage and power loss of the Bukit Kapur Belanda feeder was carried out by compensating for reactive power injection using 6 units of capacitor banks with different capacities through OCP (Optimal Capacitor Placement) analysis. The result of improving the drop voltage and power losss on the Belanda feeder, the Bukit Kapur sub feeder after being given a capacitor bank, decreased to 4.37% and the power loss decreased to 176.7 kW and 190.7 kVAR.Keywords: Drop voltage, power loss, capacitor bank, Optimal Capacitor Placement (OCP)